The synthesis of new potential photosensitizers. Part 3. Tetraphenylporphyrin esters of profens. (May 2015) - Kuś, Piotr; Kozik, Violetta; Rojkiewicz, Marcin; Sochanik, Aleksander; Szurko, Agnieszka; Kempa, Marta; Kozub, Patrycja; Rams-Baron, Marzena; Jarzembek, Krystyna; Stefaniak, Marta; Sakowicz, Julian
Abstract: Six tetraphenyl derivatives of arylpropionic acids (profens) were synthesized in search for improved novel photosensitizers that might find application in photodynamic therapy (PDT) of various cancers. Our goal was to alter hydrophobic-hydrophylic characteristics of the tetraphenylporphyrin ring by substitution with propionyl derivatives. As starting materials we used profens known primarily from their widespread use as non-steroidal anti-inflammatory drugs (ibuprofen, naproxen, ketoprofen, fenoprofen, fluorbiprofen) and 2-phenylpropionic acid (model compound). The new compounds were characterized using spectroscopic and photophysical methods with focus given to measurement of molecules' lifetime in excited triplet state, time-resolved singlet oxygen phosphorescence and measurement of photostability. Fluorescence quantum yields were also determined; data revealed no planarity changes in the porphyrin molecule following substitution with profens. Highlights: Six tetraphenyl derivatives of arylpropionic acids (profens) were synthesized. Basic physicochemical properties were determined. The compounds could be considered as potential PDT photosensitizers.